1976
DOI: 10.1203/00006450-197603000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Dietary Amino Acids for Energy Production in Neonatal Rat Liver

Abstract: Suneroxide dismutase activitv was determined in blood and lung ;issue from adults and varibus infant groups. Enzyme activity in human fetuses and infants was significantly lower than in adults. Similarly, S O D activity was related to age in rats and rabbits with much lower activity found in late fetal animals cornpared with the adult animals. No significant differences in enzyme activity, however, were seen between (I) infants with I R D S / H M D and their premature peers without I R D S / H M D and between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1977
1977
1987
1987

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Starvation induced a sharp increase in gluconeogenic ability on day 19 after birth in rats (WHITE & MILLER, 1976), this activation being, however, lower than in adults (SNELL & WALKER, 1973). This increase lowered lactate levels, not affecting those of glycerol, despite the increase found in adults with fasting (PALOU et al, 1981) because of enhanced lipolysis (KNOPP et d., 1970).…”
Section: Discussionmentioning
confidence: 91%
“…Starvation induced a sharp increase in gluconeogenic ability on day 19 after birth in rats (WHITE & MILLER, 1976), this activation being, however, lower than in adults (SNELL & WALKER, 1973). This increase lowered lactate levels, not affecting those of glycerol, despite the increase found in adults with fasting (PALOU et al, 1981) because of enhanced lipolysis (KNOPP et d., 1970).…”
Section: Discussionmentioning
confidence: 91%
“…In a recent study about hepatic amino acid utilization, White and Miller (21) concluded that 14C0, expiration tended to decline with age for alanine and leucine. However, their kinetics showed that I4CO, production was higher in 19-day-old animals than in 3-day-old newborns when measured during the first hour following injection.…”
Section: Discussionmentioning
confidence: 99%
“…This is surprising since the solid diet provides more nitrogen than maternal milk [22] and there is a parallel increase in the efficiency of the rat intestine to absorb amino acids [23,24], However, the fall in concentration of essential amino acids could be related to the increase in protein concen tration in these tissues, associated with the high protein synthesis rates reported during the weaning period [10], when concentra tions of essential amino acids in plasma are also reduced [14], The low concentrations of other amino acids may be related to a further increase in the ureogenic capabilities, since weaning results in an increased daily urinary nitrogen excretion [25]. Alanine depletion occurs both in kidney and liver, at a time when alanine aminotransferase activity in these tissues reaches adult values [6].…”
Section: Discussionmentioning
confidence: 99%
“…The variations in the hormonal environ ment during the weaning period are in accor dance with the changes in the ratio of fat/carbohydrate in the diet, since glucagon de creases and plasma insulin increases be tween 20 and 30 days after birth [3,28], with parallel maturation of the pituitary-thyroid axis during this period [29], All these endo crine events could be related to the changes in concentration of amino acids in the tis sues while, at the same time, the abundance of amino acids with a lower biological value than milk proteins [30] in the solid diet could be used mainly for energetic purposes [25].…”
Section: Discussionmentioning
confidence: 99%